Factors interfering with the adoption of good hygiene practices in public school food services in Bahia, Brazil - Ferreira, Jeane dos Santos; Araújo, Maria da Purificação Nazaré; Botelho, Raquel Braz Assunção; Zandonadi, Renata Puppin; Nakano, Eduardo Yoshio; Raposo, António; Han, Heesup; Nader, Martín; Ariza-Montes, Antonio; Akutsu, Rita de Cássia Coelho de Almeida (Frontiers in Public Health, 2022)
This cross-sectional study aimed to identify factors that interfere with the adoption of good hygiene practices in public school food services (SFS) in Bahia, Brazil. The search was conducted in public schools in Bahia/Brazil. Data collection included (i) evaluation of the adoption of Good Practices in school food services through visual observation and registration in the checklist in Good Hygienic Practices in School Food Services; (ii) Identification of schools’ foodservice physical areas and environmental comfort measures; (iii) identification of sociodemographic and occupational characteristics and assessment of attitudes and level of knowledge in food hygiene. We used a sample calculation with a confidence level of 95% and an error of 5%, which resulted in a sample of 159 schools, randomly selected by stratified probability sampling based on the number of existing schools. The classification of the sanitary status was of moderate risk in 74.8% (n=119) of the SFS (51-75% of compliance) and 25.2% (n=40) at high risk (26-50% compliance). The average percentage of compliance for the 159 SFS in the municipality was 50.23%, obtaining high-risk classification (26-50% compliance). In the SPS, the absence of dry goods’ storage, meat preparation area, and storage of residues in more than 98% of schools was observed. Accessing attitudes, 1.4% (n=2) of the food handlers were classified as unsatisfactory (0 to 49% of correct answers), 8.5% (n=12) as satisfactory with restriction (50 to 69% of correct answers) and 90.1% (n=128) as satisfactory. Considering the knowledge level, 6.3% (n=9) of the handlers had unsatisfactory knowledge (0 to 49% of correct answers), 27.5% (n=39) as satisfactory with restriction (50 to 69 % of correct answers) and 66.2% (n=94) as satisfactory. Therefore, factors that interfered in adopting good practices in the SFS were: inadequate physical structure, absence of areas in the SFS, and absence/low number of equipment to control the production process in the cold and hot chain. Food handlers showed satisfactory attitudes and level of knowledge. However, the physical structure of the SFS compromises the adoption of good practices. It puts at risk the safety of the food that is served to students at the evaluated public schools.